2022
DOI: 10.1007/s12144-022-04020-y
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life and health behavior habits during the COVID-19 pandemic: Mediating role of health values and moderating role of conscientiousness

Abstract: An increasing number of studies have explored health behavior changes since the COVID-19 outbreak, however, the potential mechanism leading to the acquisition of COVID-19-related health behavior habits remains largely underexplored. The current study aimed to investigate how meaning in life contributed to the Chinese general public’s acquisition of COVID-19-related health behavior habits, and whether health values would play a mediating role and conscientiousness would play a further moderating role in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In addition, conscientiousness is defined as being a person who has higher cognitive thinking processes, such as problem-focused coping and less avoidant coping ( Wrosch and Scheier, 2003 ). A handful of studies have also demonstrated that individuals with conscientiousness are associated with a higher willingness to acquire preventive behaviors ( Shook et al, 2020 ; Hu and Lü, 2022 ). However, to the best of our knowledge, there has been no study investigating the moderating mechanism of how conscientiousness in individuals affects the relationship between exposure to preventive health information and their risk judgment (ROB).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, conscientiousness is defined as being a person who has higher cognitive thinking processes, such as problem-focused coping and less avoidant coping ( Wrosch and Scheier, 2003 ). A handful of studies have also demonstrated that individuals with conscientiousness are associated with a higher willingness to acquire preventive behaviors ( Shook et al, 2020 ; Hu and Lü, 2022 ). However, to the best of our knowledge, there has been no study investigating the moderating mechanism of how conscientiousness in individuals affects the relationship between exposure to preventive health information and their risk judgment (ROB).…”
Section: Literature Reviewmentioning
confidence: 99%